STRENGTHENING THE SOCIAL ACTIVITY OF YOUTH STUDENTS AS A KEY FACTOR OF IMPROVING THE QUALITY OF EDUCATION (Conferencea, 2022)
The search for new effective forms of training specialists of various profiles largely consists in activating the cognitive activity of students, which provides for an organic combination of deep knowledge of theory and possession of all the practical skills and abilities necessary for training and education. Skillful use of the full potential of the educational process, the use of informal, creative means and methods of familiarizing students with values - all this makes humanitarian training a promising form of personality development for a future specialist.